Dependence of water adsorption on the surface structure of silicon wafers aged under different environmental conditions. Issue 47 (20th November 2019) - Chen, Lei; Ngo, Dien; Luo, Jiawei; Gong, Yunfei; Xiao, Chen; He, Xin; Yu, Bingjun; Qian, Linmao; Kim, Seong H.
Abstract : The structure and isotherm thickness of physisorbed water on a Si/SiO x surface depend on surface wettability and the physical structure of the oxide layer. Abstract : Most materials exposed to ambient air can adsorb water molecules and the adsorption capability strongly depends on the surface property. The water contact angle has been widely used as a measure for surface wettability; however, a question can still be asked whether the water contact angle can be used as an adequate sole predictor for water adsorption on the surface in humid air. In this paper, HF-etched silicon wafers were aged (oxidized) under different environmental conditions at room temperature to grow surface layers with varying water contact angles from ∼0° (fully hydrophilic) to ∼83° (highly hydrophobic), and water adsorption as a function of relative humidity (RH) was studied on such surfaces. The thickness and structure of the adsorbed water layer were found to depend on not only the surface wettability on each surface, but also the history of surface oxidation conditions. In particular, the silicon wafer surface oxidized in liquid water uptakes significantly more water from humid air than the fully-hydroxylated native oxide surface (SiO x /OH), even though its water contact angle is higher than that on the SiO x /OH surface. This could be attributed to the formation of a gel-like structure during oxidation in liquid water.